(untitled) (Progressive Agriculture, 2019)
The aim of this study was to assess the effect of major ingredients on the changes of fundamental quality parameters of pineapple fruit bar during preparation and storage. Four samples were prepared by using Extreme Vertex mixture taking three major ingredients namely fruit pulp, sugar and starch content as factors and non-enzymatic browning data and overall acceptability as responses. The result revealed that compositional differences of different ingredients in formulation fitted to the quadratic linear model at p<0.05. Among the four formulations the liking intensity of formulation F4 containing pineapple pulp 86%, starch 2% and sugar 12% showed the highest scores in all of the studied sensory parameters followed by F2, F3 and F1. Among the components studied, sugars irrespective of sources are the main components responsible for non-enzymatic browning whereas starch contributes to retain color by forming a protecting film around the reducing groups. Progressive Agriculture 30 (2): 227-237, 2019